A new age calibrator for red horizontal branch populations. - Hatzidimitriou, D. (1991)
A new age indicator for star clusters and other stellar populations, with red horizontal branches or clumps, is introduced. This indicator is defined as the colour difference between the median colour of the red horizontal branch or clump and the red giant branch at the level of the horizontal branch. This difference is clearly independent of the values adopted for the reddening and distance modulus of the population as well as of systematic errors in the photometry and it is shown to be insensitive to metal abundance for a wide range of metallicities from solar values down to [Fe/H]~ - 1.7 dex. The theoretical predictions of stellar evolution models for this indicator are also examined. Finally, the new indicator is applied to colour-magnitude diagrams of star clusters with poorly known ages in our Galaxy, as well as to field populations in the Magellanic Clouds and the Carina dwarf spheroidal galaxy. At least one of the galactic disc globular clusters examined is found to have an age less than ~8 Gyr.
Keywords: Astronomical Catalogs; Astrophysics; Calibrating; Color-Magnitude Diagram; Horizontal Branch Stars; Magellanic Clouds; Milky Way Galaxy; Red Giant Stars; star clusters; stellar evolution